Crystal structure of SIV matrix antigen and implications for virus assembly. - Rao, Z; Belyaev, A; Fry, E; Roy, P; Jones, I; Stuart, D (1995)
Simian immunodeficiency virus (SIV) is closely related to human immunodeficiency virus (HIV), their matrix antigens (MAs) sharing some 50% sequence identity. MA is a component of Pr55Gag, the sole protein required for assembly of the virion shell. MA targets Pr55 to the plasma membrane, and facilitates incorporation of the virus envelope protein and assembly of the Pr55Gag shell. Cleavage of Pr55 by the viral protease produces the mature protein of relative molecular mass 17-18K, which underlies the host-derived membrane and is important in both virus entry and nuclear localization of the virion core. Here we report the crystal structure of SIV MA. The molecule forms a trimer consistent with oligomerization in vitro, the observed virion architecture, and various biological properties of MA.